Using a Delphi process to develop an effective train-the-trainers program to train health and social care professionals throughout Europe - Pearce, Jennifer; Jones, Caryl; Morrison, Sinead; Olff, Miranda; van Buschbach, Susanne; Witteveen, Anke B.; Williams, Richard; Orengo-García, Francisco; Ajduković, Dean; Aker, A. Tamer; Nordanger, Dag; Lueger-Schuster, Brigitte; et al. (2012)
Research has shown that developing a Train-the-Trainers (TTT) program is important if agencies are to implement guidelines, but the most effective way to deliver a TTT program remains unanswered. This article presents data from a 3-round Internet-based Delphi process, which was used to help develop consensus-based guidelines for a TTT programme to deliver to health and social care professionals throughout Europe a curriculum on traumatic stress. In Round 1, 74 experts rated the importance of statements relating to the TTT field and then reassessed their scores in the light of others' responses in subsequent rounds. Forty-one (67%) of 61 statements achieved consensus (defined as having a mean score >7 or < 3 on the 0-9 rating scales used and 70% of participants scoring 7 and above or 3 and below) for inclusion. Key TTT components included interactive and practical presentations, delivery to groups of 7-12 people over 2 days, external and local expert facilitation, course manuals, refresher courses, and supervision. The Delphi process allowed a consensus to be achieved in an area in which there are limitations in the current evidence.
Projekt MZOS
ENG